The Differences of Natural Science and Social Science Pre-service Student’s Perceptions for Biotechnology - Hariyadi, Slamet; Wahono, Bevo; ., Suratno; Prihatin, Jekti; Siswati, Bea Hana (Universitas Islam Jember, 2023)
The study aims to investigate the importance of infusing SSI (Socioscientific Issue) into STEM (Science, Technology, Engineering, Mathematics)-based Biotechnology learning by capturing the perceptions of students in Natural Science and Social Science. This is intended to make learning more effective because it helps students to achieve the comprehension of the material being taught. The research apply mix methods by capturing quantitative and qualitative data. The quantitative data are collected from the percentage of answers from 291 students who have filled out quizzes through online surveys. While qualitative data is collected from garnering students’ answers through unstructured interviews. The results showed that students of Natural Science discussed biotechnology more technically and normatively resulting in product effects, while students of Social Science focused more on the policy and risk aspects of biotech products. It is the difference in perception between the two majors that requires the SSI approach to be infused into the STEM approach. The benefits of such infusionare improved students' HOTS (Higher Order Thinking Skills), which is in line with the current learning trend of the Industrial Revolution 4.0. Keywords: SSI, Biotechnology, STEM education, HOTS